Sexual size dimorphism in anadromous brown trout Salmo trutta. Issue 1 (11th May 2015) - Jonsson, B.; Jonsson, N.
<x xml:space="preserve">Abstract</x> Anadromous trout Salmo trutta exhibits sexual size dimorphism (SSD); females were larger than males in populations where male mean total length (LT) at maturity was below 49 cm and females were smaller than males when mean male LT was above 49 cm, the slope of the regression of female on male LT was 0·59. In streams with mean annual discharge below 41 m3 s−1, flow added significantly to a model with SSD as the dependent variable and male mean LT at maturity as the first predictor variable. There was a slight increase in SSD with increasing latitude, which may result from an increase in male size with increasing latitude.